Investigation of cord-rubber composite durability by the material force method. (15th April 2020) - Popa, C.M.; Gebhardt, C.; Raje, N.; Steenwyk, B.; Kaliske, M.
Highlights: The durability of cord-reinforced elastomers is investigated (tensile tests). The material force method is used to compute the energy release rate (crack tip). The numerical analysis is performed within the XFEM and FEM. The cord geometry's influence on the fracture behaviour is evaluated. Abstract: The research at hand deals with durability analysis of cord-reinforced elastomers using the material force concept. Different types of steel cord reinforcement are used, in order to determine the influence of the cord construction on the fracture sensitivity of the composite product. The composite is analysed using the Extended Finite Element Method to reduce the effort of the meshing process for the complex geometry of twisted reinforcing cords. Material forces are computed at the crack tip area and a qualitative ranking of the different reinforcement types is obtained. The results are successfully compared to experimental investigations.